Correlation of lipid profiles with coronary artery plaque levels in patients undergoing coronary angiography - Sedanur Uzunpolat Yayla; Ayse Semra Demi̇r Akca; Mustafa Ozan Cakir; Gozde Nur Turmus; Abdulkerim Yayla; Sema Soner Karanfi̇l; Tugba Ci̇msi̇r Soran (Medicine Science)
This study aims to observe the effect of lipid profiles (total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL), triglyceride (TG)) on coronary artery plaque rates of patients undergoing coronary angiography at Zonguldak Bulent Ecevit University (ZBEUN) Health Practice and Research Hospital. A total of 500 patients who underwent coronary angiography (CAG) between January 2019 and December 2020 at ZBEUN Health Practice and Research Hospital participated in this retrospective study. The sample of this study consists of 250 patients with a stenosis level below 50% and 250 patients with stenosis level of 50% and above according to CAG results. Information and data about the patients were accessed through the Hospital Information Management System (HIMS). The mean age of the individuals participating in the study was 63 years, the mean age of women was 65±12.3, and the mean age of men was 62±11.8. The majority of patients are men (74.2%). When we categorized the lipid profiles as low, optimal and high, LDL, triglyceride and total cholesterol values were found to be significantly higher and HDL values were found to be significantly lower in those with a stenosis degree of 50% and above (p [Med-Science 2024; 13(4.000): 937-41]